Ocular Manifestations and Visual Outcomes of Behçet's Uveitis in a Thai population. (2nd January 2019) - Pathanapitoon, Kessara; Kunavisarut, Paradee; Saravuttikul, Fa-Arun; Rothova, Aniki
ABSTRACT: Purpose: To report on ocular manifestations and visual outcomes of Thai patients with Behçet's Uveitis (BU). Methods: We reviewed medical records of 50 BU patients (31 males and 19 females). Ocular manifestations, treatment modalities, complications, and visual outcomes were registered. Results: Ocular involvement was bilateral in 76% of patients, resulting in 89 affected eyes. Panuveitis and posterior uveitis were the most common types. Retinal vasculitis was noted in majority of affected eyes and specifically arteritis was noticed in 32/57(56%). Most patients received combination therapy of systemic corticosteroids and immunosuppressive agents (azathioprine 72%). At final visit, VA ≤20/200 was observed in 25 affected eyes (28%). Risk factors for poor visual outcome were poor visual acuity at presentation ( p  < 0.001) and development of optic atrophy ( p  = 0.01). Conclusions: Typical ocular manifestations of Thai patients with BU consisted of bilateral uveitis affecting posterior eye segment with high rate of complications and frequent visual loss.